Ecosystem services—current challenges and opportunities for ecological research - Birkhofer, Klaus; Diehl, Eva; Andersson, Jesper; Ekroos, Johan; Früh-Müller, Andrea; Machnikowski, Franziska; Mader, Viktoria L.; Nilsson, Lovisa; Sasaki, Keiko; Rundlöf, Maj; Wolters, Volkmar; Smith, Henrik G. (Frontiers in Ecology and Evolution, 2015)
The concept of ecosystem services was originally developed to illustrate the benefits that natural ecosystems generate for society and to raise awareness for biodiversity and ecosystem conservation. In this article we identify major challenges and opportunities for ecologists involved in empirical or modeling ecosystem service research. The first challenge arises from the fact that the ecosystem service concept has not been generated in the context of managed systems. Ecologists need to identify the effect of anthropogenic interventions in order to propose practices to benefit service-providing organisms and associated services. The second challenge arises from the need to evaluate relationships between indicators of ecosystem services that are collected in ecological studies while accounting for uncertainties of ecological processes that underlie these services. We suggest basing the assessment of ecosystem services on the utilization of sets of indicators that cover aspects of service-providing units, ecosystem management and landscape modification. The third challenge arises from our limited understanding of the nature of relationships between services and a lack of a general statistical framework to address these links. To manage ecosystem service provisioning, ecologists need to establish whether services respond to a shared driver or if services are directly linked to each other. Finally, studies relating biodiversity to ecosystem services often focus on services at small spatial or short temporal scales, but research on the protection of services is often directed towards services providing benefits at large spatial scales. Ecological research needs to address a range of spatial and temporal scales to provide a multifaceted understanding of how nature promotes human well-being. Addressing these challenges in the future offers a unique opportunity for ecologists to act as promoters for the understanding about how to conserve benefits gained from nature.